Nuclear AgNOR protein enhancement in nucleoplasms of peripheral blood lymphocytes of babies/children with down syndrome. Issue 3 (8th January 2016) - Imamoglu, Nalan; Eroz, Recep; Canatan, Halit; Demirtas, Halil; Saatci, Çetin
ABSTRACT: Down syndrome (DS) is one of the most common chromosomal disorders. The factors contributing to the mental retardation together with other defects in this syndrome have not been fully explained. Individuals with DS have extra rRNA gene family since they carry an extra chromosome 21. The few reports available are on the relationship between the nucleolus organizer regions (NORs) and DS phenotype. The in vivo regulation of NORs expression on the extra chromosome 21 is not completely understood. Previous studies have shown that nucleoli of lymphocytes from infants (mostly neonates) with DS contain more in vivo and in vitro nucleolar AgNOR proteins when compared with healthy infants. The objective of this study is to compare the in vivo nuclear AgNOR protein level in nucleoplasms (also called as karyoplasm) of nonstimulated peripheral blood lymphocytes from babies/children with DS and healthy controls. Peripheral blood samples obtained from 20 babies/children with DS and 20 matched healthy controls were smeared on clean glass slides and then AgNOR staining was performed. The AgNOR protein level in nucleoplasms of lymphocytes from both groups was calculated using a computer program. Nearly 100 interphase nuclei per individual were analysed. Average nuclear AgNOR protein levels in nucleoplasms of lymphocytes from babies/children with DS were found to be significantly higher than those of the controls ( P < 0.001). On the basis of our present results, we propose that the increase of nuclear AgNOR protein in in vivo conditions may contribute to the formation of DS phenotypes. Microsc. Res. Tech. 79:133–139, 2016 . © 2016 Wiley Periodicals, Inc.